Liming Method and Rate Effects on Soil Acidity and Arabica Coffee Nutrition, Growth, and Yield - Parecido, Renan J. [UNESP]; Soratto, Rogério P. [UNESP]; Perdoná, Marcos J.; Gitari, Harun I.; Dognani, Victor [UNESP]; Santos, Anderson R. [UNESP]; Silveira, Lucas [UNESP] (Springer Nature, 2021)
Purpose: As soil acidity is a recurring constraint for Arabica coffee (Coffea arabica L.) yield and the application method can interfere with the liming efficiency, a field experiment was performed to evaluate the effect of broadcast- and band-applied limestone rates on amelioration of soil profile chemical characteristics and coffee nutrition, growth, and yield. Methods: The experiment took place from 2015 to 2020 on a sandy clay loam Acrisol (20% clay at 0–0.2-m depth) of southeastern Brazil. It was arranged in a randomized complete block design with three replications. The treatments comprised two limestone rates (2100 and 4200 kg ha−1), both uniformly broadcast-applied all over the area or applied as a surface band under the canopy projection of the plants, and an unamended control. Results: Liming efficiently improved soil chemical attributes up to the depth of 0.1–0.2 m, but only slightly affected the 0.2–0.4-m layer. Band-applied limestone was more efficient in reducing the acidity and increasing the concentrations of Ca2+ and Mg2+ in the soil beneath the plant canopy, while greater effects between the rows were obtained with the broadcast application. When band-applied, limestone rates higher than those currently recommended did not cause an excessive increase in soil pH or micronutrient deficiency in coffee trees and increased bean yield by 42% (589 kg ha−1). Conclusions: Concentrated (band) application of limestone was more efficient than its broadcast application to ameliorate the soil acidity in depth and over time beneath the plant canopy, as well as to increase plant growth and coffee yield.
Keywords: Application method; Coffea arabica; Mineral nutrition; Plant growth; Soil amendment